До характеристики способів захисту трудових прав державних службовців - Апанаскович, Л. В.; Apanaskovych, L. V. (Knowledge, Education, Law, Management. – 2020. – Vol. 3, № 7 (35). – P. 3-7, 2020)
Запропоновано власне визначення поняття способів захисту трудових прав державних службовців. Виокремлено та надано характеристику відповідних способів захисту. Відзначено, що перелічені у статті способи захисту трудових прав повинні використовуватись комплексно, тобто поєднуватись, що дасть змогу підвищити ефективність та результативність такого захисту. Визначено, що спосіб захисту трудових прав державних службовців найбільш доцільно розуміти як сукупність законодавчо визначених дій, які вчиняються державними службовцями та/або органами державної влади задля реалізації першими наданих їм нормами чинного законодавства повноважень під час здійснення трудової діяльності.

The relevance of the article is that the civil service is complex in nature and content, and therefore it requires a special approach to regulating the work of this category of workers, in particular the creation of the necessary conditions for them to exercise their right to work. The right of civil servants to protection of labor rights is a substantive subjective right, expressed in the ability of a civil servant to resort to certain means of protection, to apply legal measures to restore his violated or challenged right. The article, based on the analysis of scientific views of scientists, proposes the author’s definition of the concept of ways to protect the labor rights of civil servants. The characteristic methods of protection are singled out and given a description. It is noted that the methods of protection of labor rights listed in the article should be used comprehensively, i.e. combined, which will increase the efficiency and effectiveness of such protection. It is determined that the method of protection of labor rights of civil servants is most appropriate to understand as a set of legally defined actions performed by civil servants and/or public authorities to implement the first powers granted to them by current legislation during employment.

Предложено собственное определение понятия способов защиты трудовых прав государственных служащих. Выделена и предоставлена ​​характеристика соответствующих способов защиты. Отмечено, что перечисленные в статье способы защиты трудовых прав должны использоваться комплексно, то есть совмещаться, что позволит повысить эффективность и результативность такой защиты. Определено, что способ защиты трудовых прав государственных служащих наиболее целесообразно понимать как совокупность законодательно определенных действий, совершаемых государственными служащими и/или органами государственной власти для реализации первыми предоставленных им нормами действующего законодательства полномочий при осуществлении трудовой деятельности.
To the characteristics of ways to protect the labor rights of civil servants
W sprawie charakterystyki sposobów ochrony prawa pracy urzędników państwowych
Апанаскович, Л. До характеристики способів захисту трудових прав державних службовців / Людмила Апанаскович // Knowledge, Education, Law, Management. – 2020. – Vol. 3, № 7 (35). – P. 3-7. - DOI: https://doi.org/10.51647/kelm.2020.7.3.1.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; державні службовці; government officials; государственные служащие; трудові права; labor rights; трудовые права; захист трудових прав; protection of labor rights; защита трудовых прав; способи захисту трудових прав; ways of protecting labor rights; способы защиты трудовых прав; правове регулювання; legal regulation; правовое регулирование